Association of Prehypertension with Renin Angiotensin System: A Cross-Sectional Study on Tribal Population of Northern India - Vani Kandpal; Mohinder Pal Sachdeva; Kallur Nava Saraswathy (Journal of the Practice of Cardiovascular Sciences)
Introduction: Hypertension (HTN), the third risk factor driving death and disability as per Global Burden of Disease 2019, is a major public health concern. Prehypertension, the intermediate stage between HTN and normal blood pressure (BP), is associated with subclinical atherosclerosis and target-organ damage. Evaluating the prevalence of prehypertension is imperative to prevent disease progression. Prehypertension, alike HTN, is a complex disorder that manifests when genes are triggered by the environment. The current study attempts to evaluate the prevalence of prehypertension in a tribal population of Northern India. Further, the association with extensively studied renin–angiotensin system (RAS) pathway genes with prehypertension has been explored. Methods: A cross-sectional study was conducted on adults of 20–60 years old belonging to a tribal community, Rang Bhotia of Northern India. Information on demographic, lifestyle, and anthropometric risk factors was collected. The blood sample was collected for lipid and genetic analysis. DNA extraction and genotyping of five genetic markers of RAS-related pathway were performed. Chi-square and t-tests were used for assessing significant differences between the groups. Logistic regression was used to examine the association of genes with prehypertension and HTN. Results: Among 254 adults participating in the study, 39% and 42% had prehypertension and HTN, respectively. T allele of M235T genetic marker was found to be posing two-fold risk for prehypertension (odds ratio [OR] = 2.9; 95% confidence interval [CI] =1.10–7.72; P = 0.03 in dominant model and OR = 1.83; 95% CI = 1.09-3.09; P = 0.02 in additive model) after adjusting for age and sex. On the other hand, G allele of A6G polymorphism was found to be providing protection toward prehypertension (OR = 0.32; 95% CI = 0.11–0.92; P = 0.03 in recessive model and OR = 0.55; 95% CI = 0.32–0.94; P = 0.03 in additive model). Conclusion: More than one-third of individuals exhibited prehypertension, suggesting an impending burden of HTN and comorbidities among the tribal population in the near future. Moreover, increased genetic susceptibility toward elevated BP commands immediate attention. Effective management strategies including interventions on lifestyle, diet modification, and weight management need to be introduced to combat increasing HTN among the tribal population.